2014
DOI: 10.1103/physrevd.89.106006
|View full text |Cite
|
Sign up to set email alerts
|

Lifshitz effects on vector condensate induced by a magnetic field

Abstract: By numerical and analytical methods, we study in detail the effects of the Lifshitz dynamical exponent z on the vector condensate induced by an applied magnetic field in the probe limit.Concretely, in the presence of the magnetic field, we obtain the Landau level independent of z, and we also find the critical value by coupling a Maxwell complex vector field and an SU(2) field into a (3+1)-dimensional Lifshitz black hole, respectively. The research results show that for the two models with the lowest Landau le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…1(a), 1(b), and 1(c) denote the superconducting phases without superfluid velocity (i.e., S y = 0), from which we find that, when the temperature gradually decreases, there is always a critical value below which the second-order phase transition occurs. This is just the conductor-superconductor phase transition [14,17,19]. The critical temperature T 0 with S y = 0 for different values of mass is listed in Table I; it follows that the increasing mass squared m 2 makes the phase transition more difficult, which is clear from the effective mass of the vector field ρ x (r), i.e., Eq.…”
Section: Results Of Condensates With Fixed Superfluid Velocitymentioning
confidence: 95%
See 3 more Smart Citations
“…1(a), 1(b), and 1(c) denote the superconducting phases without superfluid velocity (i.e., S y = 0), from which we find that, when the temperature gradually decreases, there is always a critical value below which the second-order phase transition occurs. This is just the conductor-superconductor phase transition [14,17,19]. The critical temperature T 0 with S y = 0 for different values of mass is listed in Table I; it follows that the increasing mass squared m 2 makes the phase transition more difficult, which is clear from the effective mass of the vector field ρ x (r), i.e., Eq.…”
Section: Results Of Condensates With Fixed Superfluid Velocitymentioning
confidence: 95%
“…Interestingly, the results showed that due to the nonminimal coupling between the vector field and the Maxwell field, the increasing magnetic field can induce superconductor phase transition even without charge density, which is similar to the QCD vacuum instability triggered by the strong magnetic field to develop the ρ-meson condensate [15]. Moreover, the investigation about the response of the external magnetic field on the p-wave phase transition also showed that the SU(2) YM model is a special case of the MCV model in five-dimensional (5D) soliton and 4D Lifshitz black holes [16][17][18]. Furthermore, considering the backreaction, the MCV model exhibits the rich phase structures, especially "retrograde condensation" [19][20][21].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Other generalized investigations based on this new p-wave model can be found, for example, in Refs. [55][56][57][58][59][60][61]. Considering the increasing interest in study of the holographic p-wave model, we will also extend the study to the holographic pwave superconductor with hyperscaling violation, which has not been constructed as far as we know.…”
Section: Introductionmentioning
confidence: 99%